Time-of-day effects on short-duration maximal exercise performance - Mirizio, G. G.; Soares Mendes Nunes, R.; Araujo Vargas, D.; Foster, C.; Vieira, E. (Scientific Reports, 2020)
Time-of-day dependent fluctuations in exercise performance have been documented across different sports and seem to affect both endurance and resistance modes of exercise. Most of the studies published to date have shown that the performance in short-duration maximal exercises (i.e. less than 1 min - e.g. sprints, jumps, isometric contractions) exhibits diurnal fluctuations, peaking between 16:00 and 20:00 h. However, the time-of-day effects on short duration exercise performance may be minimized by the following factors: (1) short exposures to moderately warm and humid environments; (2) active warm-up protocols; (3) intermittent fasting conditions; (4) warming-up while listening to music; or (5) prolonged periods of training at a specific time of day. This suggests that short-duration maximal exercise performance throughout the day is controlled not only by body temperature, hormone levels, motivation and mood state but also by a versatile circadian system within skeletal muscle. The time of day at which short-duration maximal exercise is conducted represents an important variable for training prescription. However, the literature available to date lacks a specific review on this subject. Therefore, the present review aims to (1) elucidate time-of-day specific effects on short-duration maximal exercise performance and (2) discuss strategies to promote better performance in short-duration maximal exercises at different times of the day.